NADI ISTIRAHAT DAN NADI PEMULIHAN DIPENGARUHI OLEH RUTINITAS OLAHRAGA - Gusti Reka Kusuma; Sri Wahyu Basuki; Erika Diana Risanti; Budi Hernawan (Herb-Medicine Journal: Terbitan Berkala Ilmiah Herbal, Kedokteran dan Kesehatan, 2020)
The level of physical fitness in Indonesia is still poor. Research shows physical fitness 22 provinces inIndonesia is 56.07% middle, while the rest are stated as being moderate. Thera are any corelation betweenphysical fitness and pulse. Assessing the work of the heart can be seen fromthe pulse which is the propagationof the heart rate. The recovery rate is one indicator to determine the level of physical fitness. This Harvard stepup test measurement is to see how quickly the body's ability to recover after doing activities. The purpose of theauthors conducting this study was to determine the difference in mean resting pulse, recovery rate of minutes 1,2 and 3 in students who regularly exercise and do not. The research method is analytic observational using across-sectional approach. A sample of 65 students, 20 who regularly exercise and 45 students do not regularlyexercise. The results of this study were treated with the mann-whitney and t-independent test showing a restingpulse value p<0.05. Researchers concluded that there weresignificant differences in the mean resting pulse,recovery rate of minutes 1, 2 and 3 in students who routinely exercised and did not.